ON SOLVING A NONLINEAR ORDINARY DIFFERENTIAL EQUATION OF THE THIRD ORDER - Starc, Zdravko F. (Matematichki Bilten, 1997)
In this note a class of integrable nonlinear ordinary differential equation of the third order is given.